PENGARUH PEMBELAJARAN BERBASIS PROYEK DAN MINAT BELAJAR TERHADAP HASIL BELAJAR IPA PADA PESERTA DIDIK KELAS IX SMP NEGERI 2 SENGKANG KABUPATEN WAJO - Farida Farida; Helmi Helmi; Pariabti Palloan (OMEGA : JURNAL ILMU PENDIDIKAN DAN SAINS FISIKA, 2023)
This study is a quasi-experimental research that aims to examine whether there is an influence of project-based learning and learning interest on science learning outcomes in grade IX students at SMPN 2 Sengkang in Wajo Regency. The independent variables in this study were project-based learning and problem-based learning. The moderator variable was the learning interest in, while the dependent variable was the science learning outcomes on Electricity and Magnetism subject. The population of the study were all 3 classes of grade IX students at SMPN 2 Sengkang in Wajo Regency. The sample was grade IX.4 as the control class with 32 students, grade IX.3 as the experimental class with 32 students, and as a trial class was grade IX.3 with 32 students. The research data was obtained by giving a test of learning outcomes on Electricity and Magnetism subject in the form of a post test. The data analysis technique employed covariate analysis (Anacova). Based on the results of inferential statistical analysis, P = 0.004 is smaller than = 0.05. It can be concluded that the application of project - based learning has a significant influence on science learning outcomes of grade IX students at SMPN 2 Sengkang in Wajo Regency on lectricity and Magnetism.